AL-KASHF ‘AN AL-ḤAQĀIQ AL-‘ILMIYYAH FĪ AL-QUR’ĀN AL-KARĪM : (Dirāsah ‘alā al-I’jāz al-‘Ilmī fī Sūrat al-Baqarah) - Abdul Mufid (QOF, 2020)
This article aims to reveal the scientific side of the Koran in surah al-Baqarah. There are 5 (five) topics that will be examined in this research, namely the qur'anic scholarship in giving priority to the mention of hearing rather than sight, the qur'anic scholarship in telling mosquitoes, the qur'anic scholarship about the place of sunrise and sunset, the scholarship of the Koran in the prohibition of gathering with the wife during menstruation, and qur'anic scholarship in breastfeeding orders for children. This is important to do, because it is in direct contact with the Koran. The significance of this research lies in the contemporary scientific topic in the longest surah of the Koran, that is surah al-Baqarah, so the big question to be answered is what is the urgency of studying the scholarship of surah al-Baqarah? Any verses that contain scientific Is there a conflict between the scholarship of the Koran with the purpose of the turn of the Koran? Is the scholarship of surah al-Baqarah only limited to one side, or many aspects that can be studied? This research is a literature research using inductive and analytic approaches. The final result shows that the scientific side of the Koran will not be exhausted to be explored and indeed the five topk above can be scientifically proven since the revelation of the Koran until now, even until the end of time.